2020
DOI: 10.3389/fmicb.2020.610001
|View full text |Cite
|
Sign up to set email alerts
|

Culturing of “Unculturable” Subsurface Microbes: Natural Organic Carbon Source Fuels the Growth of Diverse and Distinct Bacteria From Groundwater

Abstract: Recovery and cultivation of diverse environmentally-relevant microorganisms from the terrestrial subsurface remain a challenge despite recent advances in modern molecular technology. Here, we applied complex carbon (C) sources, i.e., sediment dissolved organic matter (DOM) and bacterial cell lysate, to enrich groundwater microbial communities for 30 days. As comparisons, we also included enrichments amended with simple C sources including glucose, acetate, benzoate, oleic acid, cellulose, and mixed vitamins. O… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 55 publications
2
32
0
Order By: Relevance
“…The inter- and intra- phylotypes growth rate variations under different conditions explain the large variability of actively dividing communities’ composition, with Alteromonadales identified as key taxa that caused the largest changes in communities’ structure. The enriched BrdU-labelled community composition is consistent with results obtained with other methods to identify active taxa, such as rDNA vs. rRNA gene composition 10 , 72 , 73 , microautoradiography combined with fluorescence in situ hybridization 74 , 75 , proteomics 76 , 77 , BONCAT 78 or other enrichment experiments 79 , indicating that the method is suitable to identify and characterize active members of the prokaryotic community. In this study it is evidenced that some low abundant phylotypes (< 0.5% abundance in total communities) are relatively active, as indicated by their increased contribution to the actively dividing communities.…”
Section: Discussionsupporting
confidence: 83%
“…The inter- and intra- phylotypes growth rate variations under different conditions explain the large variability of actively dividing communities’ composition, with Alteromonadales identified as key taxa that caused the largest changes in communities’ structure. The enriched BrdU-labelled community composition is consistent with results obtained with other methods to identify active taxa, such as rDNA vs. rRNA gene composition 10 , 72 , 73 , microautoradiography combined with fluorescence in situ hybridization 74 , 75 , proteomics 76 , 77 , BONCAT 78 or other enrichment experiments 79 , indicating that the method is suitable to identify and characterize active members of the prokaryotic community. In this study it is evidenced that some low abundant phylotypes (< 0.5% abundance in total communities) are relatively active, as indicated by their increased contribution to the actively dividing communities.…”
Section: Discussionsupporting
confidence: 83%
“…A species affiliated to Armatimonas was among the most common OTUs (in relative abundance) in the rDNA large fraction of the SAS and KWK rivers, although it was in low relative abundance in the rRNA, suggesting a slow growth rate. This group (Armatimonadota) has been detected in a groundwater culture enriched with a mixture of sediment organic matter and bacterial cell lysate, and may possess the metabolic potential to utilize recalcitrant organic matter ( Wu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Marine agar 2216 (BD) or marine broth 2216 (BD) are frequently and widely used in the isolation of marine bacteria from various habitats, including seawater, sediment, or the isolation of marine bacteria associated with animals or plants ( Gram et al, 2010 ; Sanz-Sáez et al, 2020 ). Several studies revealed that adding extracted inorganic compounds from the natural environment as nutrient sources could be an effective method to isolate novel bacteria from soil ( Nguyen et al, 2018 ) and groundwater ( Wu et al, 2020 ). For example, soil nutrients extracted by autoclaving an equal mixture of water and soil were found to give higher numbers of colonies ( Taylor, 1951a ).…”
Section: Introductionmentioning
confidence: 99%